2018
DOI: 10.1021/acs.jpcc.7b09956
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Cation-Specific Effects at the Interface of Mica and Aqueous Solutions

Abstract: Ion-specific effects are ubiquitous and have gained renaissance over the past few decades while remaining largely elusive. In this work, molecular dynamics simulations have been conducted to investigate the adsorption of different metal ions at the interface of mica and aqueous solutions, and cation-specific effects abide by the sequences of Na+ > K+ > Cs+ and Cs+ > K+ > Na+ for less and more charged surfaces, respectively. Mechanisms for cation-specific effects and reversal of Hofmeister series are then addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…3). These results agree with the thermodynamic trend of cation-mica interaction 37 , where the adsorption tendency is Ca 2+ ∼ Cs + » Na + ∼ Li + .…”
Section: Resultssupporting
confidence: 89%
“…3). These results agree with the thermodynamic trend of cation-mica interaction 37 , where the adsorption tendency is Ca 2+ ∼ Cs + » Na + ∼ Li + .…”
Section: Resultssupporting
confidence: 89%
“…Such characteristics of the M + position at the tetrahedral surface of illite can be observed from the time-evolution trajectories (Figure 6), and it was very clear that Ca 2+ was located above the substitution sites, whereas Na + approached the substitution sites but was distributed near the charge sites. The distribution of cations at the siloxane surface was consistent with the available results (Bourg et al, 2017;Jia et al, 2018;Kobayashi et al, 2017;Lammers et al, 2017;Sakuma & Kawamura, 2011;Yang et al, 2020). For the CN of O W , Ca 2+ was the largest, followed by Cs + and finally K + and Na + , which had roughly the same CN values at higher concentrations.…”
Section: Variation In Local Structuresupporting
confidence: 89%
“…Later, they carried out MD simulations with other ions in group IA and IIA and found three binding types between cations and the surface: at the center of hexagon sites (IS1), on top of Al (IS2) or out from the surface (OS) and the formation of IS1 and IS2 is highly dependent on the charge density of the adsorbed ions 174 . The charge state of mica solid also affects cation adsorption; Jia et al compared Na + , K + and Cs + adsorption on mica surfaces with various charge densities and found that ion adsorption followed the sequence Na + > K + > Cs + at a low charge density surface (0.16 C/m 2 and lower) and Cs + > K + > Na + at a high one (0.24 C/m 2 and higher) 175 . Mica continues to be an important model surface, for understanding ion adsorption.…”
Section: Water/tio2 Interfacesmentioning
confidence: 99%
“…174 The charge state of mica solid also affects cation adsorption; Jia et al compared Na + , K + and Cs + adsorption on mica surfaces with various charge densities and found that ion adsorption followed the sequence Na + > K + > Cs + at a low charge density surface (0.16 C/m 2 and lower) and Cs + > K + > Na + at a high one (0.24 C/m 2 and higher). 175 Mica continues to be an important model surface, for understanding ion adsorption.…”
Section: (Siomentioning
confidence: 99%